Negative electrode material of three-dimensional structure graphene coated nano silicon, preparation method of negative electrode material, lithium ion battery negative electrode plate and lithium ion battery

By modifying the three-dimensional structural composite of nano-silicon and graphene oxide, using electrostatic self-assembly and freeze-drying heat treatment, the problem of low cycling performance caused by the volume changes of the silicon material of the lithium-ion battery negative electrode material is solved, and higher cycling stability is achieved and simplified preparation process.

CN119208570APending Publication Date: 2024-12-27CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1

Patent Information

Application Number
CN202411360138.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-25
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The silicon material of the negative electrode material of lithium-ion battery has a large volume change during the electrochemical cycle, resulting in unstable SEI film formation and low battery cycle performance. The existing complex preparation methods cannot meet commercial needs.

Method used

Using a three-dimensional structural composite of modified nanosilicon and graphene oxide, the electrostatic self-assembly of positively charged modified nanosilicon and negatively charged graphene oxide is formed by electrostatic self-assembly through electrostatic self-assembly and freeze-drying heat treatment methods to prevent nanosilicon The volume of the SEI film expands and cracks, and forms a uniform SEI film.

Benefits of technology

It improves the circulation performance and stability of lithium-ion batteries, simplifies the preparation process, and meets the energy density improvement needs of commercial lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208570A_ABST
    Figure CN119208570A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses a three-dimensional structure graphene coated nano silicon negative electrode material and a preparation method thereof, a lithium ion battery negative electrode plate and a lithium ion battery. The negative electrode material comprises modified nano silicon and graphene oxide coating the modified nano silicon; the weight ratio of the modified nano silicon to the graphene oxide is (10-1): 1. The modified nano silicon with positive charges and the graphene oxide with negative charges generate electrostatic self-assembly, so that the nano silicon is fully coated with the graphene, volume expansion and cracking of the nano silicon and formation of a non-uniform SEI film can be effectively prevented, and the lithium ion battery containing the negative electrode material has improved cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a negative electrode material of three-dimensional graphene-coated nano-silicon and a preparation method thereof, a negative electrode sheet of a lithium-ion battery and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries have been popular since their introduction. However, with the development and widespread application of high-performance electric vehicles, current commercial lithium-ion batteries can no longer meet market demand, and the development of high-capacity negative electrode materials is urgent. At present, the energy density of lithium-ion batteries with traditional carbon-based negative electrodes and transition metal oxide negative electrodes is close to the theoretical energy density. Academia and industry have put forward new expectations and requirements for the energy density of high-performance lithium-ion batteries. The energy density of lithium-ion batteries is closely related to the specific capacity of electrode materials. In order to improve the energy density of lithium-ion batteries, the specific capacity of their negative electrode materials must be improved. Because, compared with positive electrode materials, negative electrode materials have greater room for capacity improvement.

[0003] Silicon materials are considered to be an excellent substitute for graphite materials. However, compared with the embedded graphite negative electrode, silicon will cause a large volume change (>300%) during the lithium ion insertion and deinsertion process. During the electrochemical cycle, the silicon material will repeatedly produce a large volume change. This volume change will not only cause repeated cracking and fragmentation of silicon, but also cause the disintegration, fracture and electrical insulation of the silicon material and the current collector. Continuous fragmentation will also cause continuous damage to the solid electrolyte interface layer (SEI) and surface rupture, causing the active material to continue to contact with the electrolyte, resulting in rapid consumption of the electrolyte and lithium ions. Therefore, the severe volume change of the silicon negative electrode will produce an unstable SEI film and cause repeated fragmentation of the SEI film, resulting in low initial coulombic efficiency (ICE) of the battery and rapid capacity decay.

[0004] To alleviate the above problems, some advanced material design strategies have been proposed. However, the preparation process of these advanced materials is too complicated, and the surface loading and volume energy density of active materials are too low to meet the requirements of commercialization. In addition, the initial Coulomb efficiency of silicon materials is very low, which will reduce the actual energy density of the entire battery.

[0005] CN110048098A discloses a method for preparing a nitrogen-doped graphene-coated nano-silicon composite material, comprising the following steps: 1) dispersing a cationic surfactant and nano-silicon in a solvent, drying, and obtaining modified nano-silicon; 2) dispersing graphene oxide in a solvent, mixing with modified nano-silicon, and drying to obtain a coating; 3) subjecting the coating to nitrogen doping treatment to obtain a nitrogen-doped graphene-coated nano-silicon composite material. The composite electrical material obtained by the present invention exhibits high charge and discharge specific capacity, coulomb efficiency, and excellent cycle stability. However, the preparation method of the composite material is relatively complicated, and nitrogen doping treatment is required to achieve its technical effect, while the preparation method adopted in the present application is relatively simple, and nitrogen doping treatment is not required.

[0006] Therefore, there is an urgent need to develop a three-dimensional graphene-coated nano-silicon negative electrode material and a preparation method thereof, a lithium-ion battery negative electrode sheet and a lithium-ion battery that have excellent cycle performance. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem in the prior art that the silicon material in the negative electrode material of a lithium battery is easy to expand and crack and form an uneven SEI film, resulting in low cycle performance of the lithium battery, and to provide a lithium ion battery negative electrode material and a preparation method thereof, a lithium ion battery negative electrode sheet and a lithium ion battery.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a negative electrode material for a lithium ion battery, wherein the negative electrode material comprises modified nano-silicon and graphene oxide coated on the modified nano-silicon;

[0009] The weight ratio of the modified nano-silicon to graphene oxide is (10-1):1.

[0010] A second aspect of the present invention provides a method for preparing a negative electrode material for a lithium ion battery, wherein the preparation method comprises the following steps:

[0011] 1) dispersing a surface modifier and nano-silicon in a buffer solution to obtain modified nano-silicon;

[0012] 2) mixing the modified nano-silicon solution containing the modified nano-silicon with the graphene oxide solution to obtain a mixed solution A, and drying to obtain a negative electrode material;

[0013] Wherein, in step 2), the Zeta potential of the mixed solution A is 15-45 mV;

[0014] The drying process includes freeze drying and heat treatment; the freeze drying conditions include a temperature of -30°C to -50°C and a time of 24-48 hours.

[0015] The third aspect of the present invention provides a negative electrode material prepared by the above preparation method.

[0016] A fourth aspect of the present invention provides a negative electrode plate for a lithium ion battery, wherein the negative electrode plate for the lithium ion battery comprises the negative electrode material described above.

[0017] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0018] Through the above technical solution, the technical solution provided by the present invention achieves the following beneficial effects:

[0019] (1) The negative electrode material provided by the present invention comprises modified nano-silicon and graphene oxide coated on the modified nano-silicon. The positively charged modified nano-silicon and the negatively charged graphene oxide generate electrostatic self-assembly, so that the graphene fully coats the nano-silicon, thereby effectively preventing the volume expansion and cracking of the nano-silicon and forming an uneven SEI film, so that the lithium ion battery containing the negative electrode material has improved cycle performance.

[0020] (2) The preparation method of the negative electrode material provided by the present invention forms a 3D structure of the negative electrode material through freeze drying; through heat treatment, the oxygen-containing functional groups of graphene oxide in the negative electrode material can be removed and the interlayer spacing of graphene oxide can be reduced, so that the graphene can more fully cover the nano-silicon, thereby improving the cycle stability of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the negative electrode material prepared in Example 1 of the present invention with a scale of 50 nm;

[0022] Figure 2 This is a SEM image of the negative electrode material prepared in Example 1 of the present invention with a scale of 100 nm;

[0023] Figure 3 This is the XRD pattern of the negative electrode material prepared in Example 1 of the present invention;

[0024] Figure 4 This is a graph showing the electrochemical performance of a battery containing the negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] A first aspect of the present invention provides a negative electrode material for a lithium ion battery, wherein the negative electrode material comprises modified nano-silicon and graphene oxide coated on the modified nano-silicon;

[0027] The weight ratio of the modified nano-silicon to graphene oxide is (10-1):1.

[0028] In the present invention, the negative electrode material provided by the present invention comprises modified nano-silicon and graphene oxide coated on the modified nano-silicon, and the weight ratio of the modified nano-silicon to the graphene oxide is controlled to be (10-1):1, which can ensure that the positively charged modified nano-silicon and the negatively charged graphene oxide produce electrostatic self-assembly, so that the graphene fully coats the modified nano-silicon, thereby effectively preventing the volume expansion and cracking of the modified nano-silicon and forming an uneven SEI film, so that the lithium ion battery containing the negative electrode material has improved cycle performance.

[0029] Furthermore, the weight ratio of the modified nano-silicon to graphene oxide is (10-2):1.

[0030] In the present invention, the weight of the modified nano-silicon and graphene oxide contained in the negative electrode material is measured by a thermogravimetric analyzer (TGA / DSC 3 + ) for determination.

[0031] According to the present invention, the modified nano-silicon comprises silicon and nitrogen. The nitrogen is introduced into the modified nano-silicon in the form of amino groups by contacting the nano-silicon with a surfactant containing nitrogen. In the modified nano-silicon, amino groups are grafted onto the surface of the bulk material of the nano-silicon, so that positive charges are attached to its surface.

[0032] According to the present invention, based on the total weight of the modified nano-silicon, the modified nano-silicon contains 75-86 wt % of silicon and 14-25 wt % of nitrogen.

[0033] Furthermore, based on the total weight of the modified nano-silicon, the modified nano-silicon contains 78-82 wt % of silicon and 18-22 wt % of nitrogen.

[0034] In the present invention, the weight of silicon and nitrogen in the modified nano-silicon is measured using an inductively coupled plasma spectrometer (Agilent 725ES & Agilent 5110).

[0035] According to the present invention, the average particle size D50 of the negative electrode material is 100-500 nm, preferably 200-400 nm.

[0036] In the present invention, the average particle size of the negative electrode material is measured using a field emission scanning electron microscope (Hitachi, Japan).

[0037] A second aspect of the present invention provides a method for preparing a negative electrode material for a lithium ion battery, wherein the preparation method comprises the following steps:

[0038] 1) dispersing a surface modifier and nano-silicon in a buffer solution to obtain modified nano-silicon;

[0039] 2) mixing the modified nano-silicon solution containing the modified nano-silicon with the graphene oxide solution to obtain a mixed solution A, and drying to obtain a negative electrode material;

[0040] Wherein, in step 2), the Zeta potential of the mixed solution A is 15-45 mV;

[0041] The drying process includes freeze drying and heat treatment; the freeze drying conditions include a temperature of -30°C to -50°C and a time of 24-48 hours.

[0042] In the present invention, when the Zeta potential of the mixed solution A satisfies the above range, the electrostatic self-assembly of the modified nano-silicon and the graphene oxide is completed and evenly dispersed. Since graphene oxide is negatively charged in the aqueous solution, when the Zeta potential of the mixed solution is positive, it indicates that the modified nano-silicon is successfully prepared and the assembled composite material is evenly dispersed.

[0043] In the present invention, when the freeze-drying conditions meet the above range, the chemical composition and 3D structure formed when the modified nano-silicon and graphene oxide are composited can be better maintained, and the 3D structure is effective for the composite material as a negative electrode material for lithium-ion batteries, which is conducive to the improvement of the performance of the composite material and greatly improves the use value of the silicon material as a negative electrode for lithium batteries. The 3D structure is obtained by cooling the water in the mixed solution A and freezing it into a solid, and then sublimating the solid formed by the frozen water into water vapor, while the mixture of modified nano-silicon and graphene oxide remains in the ice shelf during freezing.

[0044] According to the present invention, the buffer solution is tris(hydroxymethyl)aminomethane hydrochloride, and the effective buffering range is pH 7-9, which is weakly alkaline.

[0045] According to the present invention, in step 1), the mass volume ratio of the nano-silicon, the surface modifier and the buffer solution is 1:(4-8):(100-300), (mg:mg:mL), preferably 1:(6-8):(100-200), (mg:mg:mL).

[0046] In the present invention, when the mass volume ratio of the nano-silicon, the surface modifier and the buffer solution meets the above range, the surface of the bulk material of the nano-silicon can be better grafted with amino groups, so that positive charges are attached to its surface, preparing for the subsequent electrostatic self-assembly.

[0047] According to the present invention, the average particle size D50 of the nano-silicon is 100-500 nm, preferably 100-200 nm.

[0048] According to the present invention, in step 1), the surface modifier is selected from at least one of polydiallyldimethylammonium chloride, 3-aminopropyltriethoxysilane and ethylenediamine.

[0049] According to the present invention, in step 1), the dispersion process includes ultrasonic dispersion, wherein the conditions of the ultrasonic dispersion include: the power of the first ultrasound is 1000-2000W, preferably 1500-2000W; the frequency of the first ultrasound is 50-100kHz, preferably 70-80kHz; the time of the first ultrasound is 30-60min, preferably 40-50min.

[0050] According to the present invention, in step 1), the dispersion process further comprises: centrifugation, washing and drying.

[0051] According to the present invention, in step 1), the washing process comprises: washing the solid obtained by centrifugation with deionized water until the pH of the washing solution is 7.5-8.

[0052] According to the present invention, in step 2), the concentration of the graphene oxide solution is 2-5 mg / mL.

[0053] In the present invention, when the concentration of the graphene oxide solution meets the above range, it can be well dispersed; when the concentration is too small, the solution is too dilute, the self-assembly process is slow and the dispersion is uneven; when the concentration is too large, the solution is too thick, and the graphene oxide cannot be evenly dispersed, resulting in an uneven composite material.

[0054] According to the present invention, in step 2), the concentration of the modified nano-silicon solution is 2-4 mg / mL.

[0055] In the present invention, when the concentration of the modified nano-silicon solution meets the above range, it can be well dispersed; due to the strong electronegativity of the surface of the modified nano-silicon, when the solution concentration is high, it cannot be evenly dispersed, and thus cannot be evenly compounded with graphene oxide, affecting its electrochemical properties.

[0056] According to the present invention, the volume ratio of the modified nano-silicon solution to the graphene oxide solution is (10-2):1.

[0057] According to the present invention, in step 2), the Zeta potential of the mixed solution A is 30-40 mV.

[0058] According to the present invention, in step 2), the mixing is carried out under ultrasonic conditions, and the ultrasonic conditions include: the power of the second ultrasound is 1000-2000W, preferably 1500-2000W; the frequency of the second ultrasound is 50-100kHz, preferably 70-80kHz; the time of the second ultrasound is 60-120min, preferably 80-100min.

[0059] According to the present invention, in step 2), the freeze-drying conditions include: temperature of -35°C to -45°C, and time of 36-48h.

[0060] According to the present invention, the heat treatment conditions include: heating from room temperature to 450-650°C at a heating rate of 3-5°C / min under protective gas for 1-2 hours. Room temperature refers to 25-35°C.

[0061] In the present invention, when the conditions of the heat treatment meet the above range, firstly, under the high-temperature protective atmosphere, the oxygen-containing functional groups of the graphene oxide are removed, which helps to improve the conductivity of the composite material; secondly, as the insulation time increases, the spacing between the graphene oxide sheets gradually decreases, which helps the modified nano-silicon to fit tightly to the graphene oxide, thereby making the composite material preparation perfect.

[0062] Furthermore, the heat treatment conditions include: under protective gas, heating from room temperature to 550-600° C. at a heating rate of 4-5° C. / min for 1.3-1.7 h.

[0063] According to the present invention, the protective gas is selected from argon and / or helium.

[0064] The third aspect of the present invention provides a negative electrode material prepared by the above preparation method.

[0065] A fourth aspect of the present invention provides a negative electrode plate for a lithium ion battery, wherein the negative electrode plate for the lithium ion battery comprises the negative electrode material described above.

[0066] According to the present invention, a method for preparing a negative electrode sheet of a lithium ion battery comprises the following steps:

[0067] The negative electrode material, conductive agent Super P and lithium polyacrylate were weighed and mixed into a slurry in a mass ratio of 8:1:1, coated on a copper foil, vacuum dried and rolled to form a negative electrode sheet for a lithium-ion battery.

[0068] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0069] According to the present invention, a method for preparing a lithium ion battery comprises the following steps:

[0070] A lithium-ion battery negative electrode sheet including a negative electrode material is used, a metal lithium sheet is used as the positive electrode, Ceglard2500 is used as a diaphragm, and a 1M LiPF6 dimethyl carbonate solution is used as the electrolyte (wherein the solvent is ethylene carbonate: diethyl carbonate = 1:1 Vol%, 10% ethylene carbonate is added, and the solute is LiPF6), and a button battery is assembled in an argon glove box.

[0071] The present invention will be described in detail below by way of examples. In the following examples,

[0072] The Zeta potential of mixed solution A was measured by a Malvern Zetasizer Nano ZS instrument;

[0073] The specific capacity was measured by Wuhan Blue Electric CT3002A instrument;

[0074] The raw materials used in the examples and comparative examples are all commercially available.

[0075] Example 1

[0076] 1) dispersing polydiallyldimethylammonium chloride and nano-silicon with an average particle size of 150 nm in a tris(hydroxymethyl)aminomethane hydrochloride solution with a pH value of 8 at a first ultrasonic power of 1700 W, a first ultrasonic frequency of 75 kHz, and a first ultrasonic time of 45 min, centrifuging to obtain a solid, washing the solid obtained by centrifugation with deionized water until the pH value of the washing solution is 7.5, and drying to obtain modified nano-silicon, wherein the mass volume ratio of nano-silicon, surface modifier and buffer solution is 1:7:150 (mg:mg:mL);

[0077] 2) mixing a graphene oxide solution having a volume of 10 mL and a concentration of 3 mg / mL with a modified nano-silicon solution having a volume of 25 mL and a concentration of 3 mg / mL at a second ultrasonic power of 1700 W, a second ultrasonic frequency of 80 kHz, and a second ultrasonic time of 90 min to obtain a mixed solution A, wherein the Zate potential of the mixed solution A is 35 mV;

[0078] 3) After freeze-drying the mixed solution A at -40°C for 42 hours, heat-treating the mixed solution A at a heating rate of 4.5°C / min from 30°C to 580°C for 1.5 hours under argon protective gas to obtain negative electrode material A1;

[0079] A1 was subjected to scanning electron microscopy observation and XRD analysis, as well as electrochemical performance testing. Figure 1 This is a SEM image of the negative electrode material prepared in Example 1 of the present invention with a scale of 50 nm. Figure 1 It can be seen that the modified nano-silicon has been coated by graphene oxide, and the coating effect is good. The modified nano-silicon is evenly distributed between the graphene oxide layers.

[0080] Figure 2 The SEM image of the negative electrode material prepared in Example 1 of the present invention with a scale of 100 nm is shown in FIG. Figure 2 It can be seen that the modified nano-silicon has been coated by graphene oxide, and the coating effect is good. The modified nano-silicon is evenly distributed between the graphene oxide layers.

[0081] Figure 3 is the XRD pattern of the negative electrode material prepared in Example 1 of the present invention, Figure 3 It can be seen that after the modified nano-silicon and graphene oxide are composited, there is no other phase except the phase of modified nano-silicon and graphene oxide;

[0082] Figure 4 The electrochemical performance test diagram of the battery containing the negative electrode material prepared in Example 1 of the present invention is shown in FIG. Figure 4 It can be seen that the first reversible specific capacity is 1850 mAh / g. After 50 cycles, the reversible specific capacity of the composite material is 1205 mAh / g, and the cycle performance is good.

[0083] Example 2

[0084] 1) dispersing polydiallyldimethylammonium chloride and nano-silicon with an average particle size of 400 nm in a tris(hydroxymethyl)aminomethane hydrochloride solution with a pH value of 8 at a first ultrasonic power of 2000 W, a first ultrasonic frequency of 100 kHz, and a first ultrasonic time of 30 min, centrifuging to obtain a solid, washing the solid obtained by centrifugation with deionized water until the pH value of the washing solution is 8, and drying to obtain modified nano-silicon, wherein the mass volume ratio of nano-silicon, surface modifier and buffer solution is 1:8:300 (mg:mg:mL);

[0085] 2) mixing a graphene oxide solution having a volume of 10 mL and a concentration of 4 mg / mL with a modified nano-silicon solution having a volume of 40 mL and a concentration of 4 mg / mL at a second ultrasonic power of 2000 W, a second ultrasonic frequency of 100 kHz, and a second ultrasonic time of 60 min to obtain a mixed solution A, wherein the Zate potential of the mixed solution A is 45 mV;

[0086] 3) After freeze-drying the mixed solution A at -50°C for 24 hours, heat treatment was performed under helium protective gas at a heating rate of 5°C / min from 35°C to 650°C for 1 hour to obtain negative electrode material A2.

[0087] Example 3

[0088] 1) dispersing 3-aminopropyltriethoxysilane and nano-silicon with an average particle size of 100 nm in a tris(hydroxymethyl)aminomethane hydrochloride solution with a pH value of 9 at a first ultrasonic power of 1000 W, a first ultrasonic frequency of 50 kHz, and a first ultrasonic time of 60 min, centrifuging to obtain a solid, washing the solid obtained by centrifugation with deionized water until the pH value of the washing solution is 7.5, and drying to obtain modified nano-silicon, wherein the mass volume ratio of the nano-silicon, the surface modifier, and the buffer solution is 1:4:100 (mg:mg:mL);

[0089] 2) mixing a graphene oxide solution having a volume of 10 mL and a concentration of 2 mg / mL with a modified nano-silicon solution having a volume of 30 mL and a concentration of 2 mg / mL at a second ultrasonic power of 1000 W, a second ultrasonic frequency of 50 kHz, and a second ultrasonic time of 120 min to obtain a mixed solution A, wherein the Zate potential of the mixed solution A is 15 mV;

[0090] 3) After freeze-drying the mixed solution A at -30°C for 48 hours, heat treatment was performed under argon protective gas at a heating rate of 3°C / min from 30°C to 450°C for 2 hours to obtain negative electrode material A3.

[0091] According to the analysis and characterization method of A1, the negative electrode materials A2-A3 were analyzed and characterized. The modified nano-silicon in the negative electrode material has been coated with graphene oxide, and the coating effect is good. The modified nano-silicon is evenly distributed between the graphene oxide layers, so that the batteries containing the negative electrode material have excellent electrochemical properties.

[0092] Comparative Example 1

[0093] The negative electrode material was prepared according to the method of Example 1, except that the volume of the graphene oxide solution was 37.5 mL, and the Zeta potential of the mixed solution A was -5 mV, to obtain the negative electrode material D1.

[0094] Comparative Example 2

[0095] The negative electrode material was prepared according to the method of Example 1, except that the mixed solution A was dried at 20° C. for 40 h to obtain the negative electrode material D2.

[0096] Test Example 1

[0097] The physical properties of the negative electrode materials in the above embodiments and comparative examples were tested.

[0098] The weight of the modified nano-silicon and graphene oxide of the negative electrode material was measured by thermogravimetric analysis (TGA / DSC 3 + ) for testing;

[0099] The average particle size D50 of the negative electrode material was measured using a field emission scanning electron microscope (Hitachi, Japan);

[0100] The weight of silicon and nitrogen in the modified nano-silicon was measured using an inductively coupled plasma spectrometer (Agilent 725ES & Agilent 5110);

[0101] The results are shown in Table 1.

[0102] Table 1 Negative electrode material characteristic test results

[0103]

[0104] Test Example 2

[0105] The negative electrode materials (A1-A3 and D1-D2) prepared in Example 13 and Comparative Example 12 were subjected to electrochemical performance tests.

[0106] Assembling Li-ion Batteries:

[0107] (1) Weighing negative electrode materials (A1-A3 and D1-D2), conductive agent Super P and lithium polyacrylate in a mass ratio of 8:1:1 respectively to form a slurry, coating it on a copper foil, vacuum drying it, and rolling it to make a negative electrode sheet for a lithium-ion battery;

[0108] (2) A lithium-ion battery negative electrode sheet including a negative electrode material was used, a metal lithium sheet was used as a positive electrode, Ceglard 2500 was used as a separator, and a 1M LiPF6 dimethyl carbonate solution was used as an electrolyte (wherein the solvent was ethylene carbonate: diethyl carbonate = 1:1 Vol%, 10% ethylene carbonate was added, and the solute was LiPF6), and button cells (A1-A3 and D1-D2) were assembled in an argon glove box.

[0109] Constant current charge and discharge test of the battery: Wuhan Blue Electric CT3002A instrument is used for testing. The test method is as follows:

[0110] After the battery was left to rest for 8 hours, it was charged and discharged at a rate of 0.3C. The test voltage range was 0.001V-1.5V, and the 1C current density was defined as 2000mA / g.

[0111] Table 2 Electrochemical performance test results

[0112] serial number First reversible specific capacity (mAh / g) After 50 cycles, reversible specific capacity (mAh / g) A1 1850 1205 A2 1800 1117 A3 1750 1056 D1 1456 700 D2 1557 736

[0113] It can be seen from Table 1-2 that the weight ratio of modified nano-silicon to graphene oxide in the negative electrode materials of lithium-ion batteries prepared in Examples 1-3 of the present invention is appropriate, and excellent cycle performance is achieved.

[0114] Compared with Comparative Example 1, the volume of the graphene oxide solution in Comparative Example 1 is 37.5 mL, and the Zeta potential of the mixed solution A is negative, so that the weight ratio of modified nano-silicon to graphene oxide in the negative electrode material of the lithium ion battery prepared in Comparative Example 1 is not within the protection scope of the present application, resulting in the modified nano-silicon and graphene oxide not being completely electrostatically self-assembled and being unevenly dispersed, and the volume expansion and cracking of nano-silicon cannot be effectively prevented and an uneven SEI film is formed, so that the prepared lithium ion battery has poor cycle performance.

[0115] Compared with Example 2, Example 1 adopts freeze-drying while Example 2 adopts the mixed solution A to be dried at 20°C for 40h. The chemical composition and three-dimensional structure formed when the modified nano-silicon and graphene oxide are compounded can be better maintained, while Comparative Example 2 cannot form a 3D structure, so that the prepared lithium-ion battery has poor cycle performance.

[0116] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material comprises modified nano-silicon and graphene oxide coated on the modified nano-silicon; The weight ratio of the modified nano-silicon to graphene oxide is (10-1):

1.

2. The negative electrode material according to claim 1, wherein The weight ratio of the modified nano-silicon to graphene oxide is (10-2):1; And / or, the modified nano-silicon comprises silicon and nitrogen; Preferably, based on the total weight of the modified nano-silicon, the modified nano-silicon contains 75-86 wt % of silicon and 14-25 wt % of nitrogen.

3. The negative electrode material according to claim 1 or 2, wherein The average particle size D50 of the negative electrode material is 100-500 nm, preferably 200-400 nm.

4. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The preparation method comprises the following steps: 1) dispersing a surface modifier and nano-silicon in a buffer solution to obtain modified nano-silicon; 2) mixing the modified nano-silicon solution containing the modified nano-silicon with the graphene oxide solution to obtain a mixed solution A, and drying to obtain a negative electrode material; Wherein, in step 2), the Zeta potential of the mixed solution A is 15-45 mV; The drying process includes freeze drying and heat treatment; the freeze drying conditions include a temperature of -30°C to -50°C and a time of 24-48 hours.

5. The preparation method according to claim 4, wherein In step 1), the mass volume ratio of the nano-silicon, the surface modifier and the buffer solution is 1:(4-8):(100-300), (mg:mg:mL); And / or, the average particle size of the nano-silicon is 100-500nm, preferably 100-200nm; and / or, the surface modifier is selected from at least one of polydiallyldimethylammonium chloride, 3-aminopropyltriethoxysilane and ethylenediamine; And / or, the dispersion process includes ultrasonic dispersion, wherein the conditions of the ultrasonic dispersion include: the power of the first ultrasound is 1000-2000W, the frequency of the first ultrasound is 50-100kHz, and the time of the first ultrasound is 30-60min; And / or, the dispersion process further includes: centrifugation, washing and drying.

6. The preparation method according to claim 4 or 5, wherein: In step 2), the concentration of the graphene oxide solution is 2-5 mg / mL; and / or, the concentration of the modified nano-silicon solution is 2-4 mg / mL; And / or, the volume ratio of the modified nano-silicon solution to the graphene oxide solution is (10-2):1; And / or, the Zeta potential of the mixed solution A is 30-40 mV; And / or, the mixing is performed under ultrasonic conditions, and the ultrasonic conditions include: the power of the second ultrasound is 1000-2000W, the frequency of the second ultrasound is 200-300kHz, and the time of the second ultrasound is 60-120min.

7. The preparation method according to any one of claims 4 to 6, wherein: In step 2), the freeze-drying conditions include: temperature of -35°C to -45°C, time of 36-48h; Preferably, the heat treatment conditions include: under protective gas, heating from room temperature to 450-650°C at a heating rate of 3-5°C / min for 1-2h; Preferably, the protective gas is selected from argon and / or helium.

8. A negative electrode material obtained by the preparation method according to any one of claims 4 to 7.

9. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate of the lithium-ion battery comprises the negative electrode material described in any one of claims 1 to 3 and 8 above.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped graphene-coated nano-silicon composite material

    CN110048098A

Cited By

  • Preparation method and application of silicon-carbon negative electrode material based on two-step liquid-phase electrostatic self-assembly

    CN120473496A